DNA Barcodes Identify the Larvae and Unassociated Male of Three Onycholyda Sawflies (Hymenoptera, Pamphiliidae) from China - Shinohara, Akihiko; Kakuda, Tsuneo; Wei, Meicai; Kameda, Yuichi (Zootaxa, 2018)
A molecular analysis based on mitochondrial cytochrome oxidase subunit 1 (COI) gene sequences has indicated that larvae collected in Sichuan and Zhejiang Provinces, China, belong to Onycholyda xanthogaster Shinohara, 1999, and O. fulvicornis Shinohara, in Shinohara & Wei, 2016 (Hymenoptera, Pamphiliidae), and that a male Onycholyda specimen from Mt. Tianmushan, Zhejiang Province is the hitherto unknown male of O. tianmushana Shinohara & Xiao, 2006. The first host plant records are Rubus inopertus (Focke) Focke (Rosaceae) for O. xanthogaster and Rubus hirsutus Thunb. for O. fulvicornis. The larvae of O. xanthogaster and O. fulvicornis are briefly described and O. xanthogaster is newly recorded from Sichuan Province. The male of O. tianmushana is described for the first time.